Cigarette smoking amongst Rheumatoid Arthritis patients in a tertiary centre in South Africa - le Roux, Simon (Department of Medicine, 2024)
Background: Cigarette smoking is associated with worse outcomes amongst rheumatoid arthritis (RA) sufferers, with poorer disease control, increased extra-articular complications and comorbidities. There are currently no data from sub-Saharan Africa. Objective: To describe the prevalence of cigarette smoking, and explore disease control, comorbidities, extra-articular disease, and attitudes of smokers to their habit amongst RA patients in an outpatient clinic at tertiary level public hospital in South Africa. Further, we asked patients about the impact of prohibition during the COVID pandemic. Methods: A cross-sectional study of consenting adult outpatients with RA meeting the EULAR/ACR 2010 Classification Criteria. Demographic, clinical and patient-reported outcome measures (PROMs) together with a questionnaire about smoking and Fagerström test for nicotine dependence were collated. (1) Results: Of 632 patients (536 females), the mean (SD) age and disease duration were 55.4 (13.0) and 10.1 (9.3) years. The mean (SD) Clinical Disease Activity Index (CDAI) and HAQ-DI were 14.3 (11.8) and 1.5 (0.7). The cohort included 218 (34,5%) smokers, and 89 (14.1%) exsmokers, and more males smoked (p=0,0002). Compared to non- or ex-smokers, smokers had lower BMI (29.7 vs 32.9 p= 0.01), higher anxiety scores (p=0,048) and incidence of COPD (8,26 % vs 2,66%, p< 0.005). Smokers were more likely than non-smokers to have a positive Rheumatoid Factor (80,3% vs 69,8%, p=0.006). There were no significant differences in age of RA onset, disease duration, SES, number of comorbidities, CDAI nor its individual components, extra-articular diseases nor in HAQ-DI, FACIT, depression nor pain scores. Of 160 patients who completed the smoking questionnaire, only 83 (49,5%) believed smoking worsened their arthritis, yet 119 (71,6%) reported receiving smoking cessation advice at the RA clinic. Participants' most common reasons for smoking were emotional support (45.8%), nicotine craving (30.5%) and pain control (25,2%). The Fagerström score revealed mild, moderate and severe nicotine dependence in 67.5%, 24.4%, and 7.5% respectively. Although 50.1% felt that living with RA made quitting difficult, 86.9% had considered quitting, and almost half (45.6%) had previously quit for more than 3 months. Conclusion: In this cohort of RA patients, a third actively smoke. Smoking is a modifiable risk factor, although half of the smokers reported that their RA made quitting difficult despite only 7.5% having severe nicotine addiction. Adequate disease control along with behavioural support should be the basis of engaging around tobacco cessation.